The Effect of Twin Date Event Day Promos, Flash Sale, and Shopee Live Discount Vouchers on Product Purchase Decisions for Shopee E-Commerce Users in the Kepung District Area - Sari, Refita; Susi Damayanti (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : The purpose of this study is to analyze the influence of Twin Date Event Day promotions, Flash Sale, and Shopee Live Discount Vouchers on purchase decisions. And to measure the role of the promotion in increasing consumer interest and purchase decisions in non-urban areas such as Kepung District. Design/Methode/Approach : Using a quantitative approach of causality type with the population of shopee E-commerce users in the Kepung District area. Where the samples taken were 40 respondents with the Purposive sampling technique, where the sampling technique was to use certain considerations. The data collection technique in this study uses a questionnaire, and the data analysis technique uses multiple linear regression analysis. Research Finding : The results of the analysis show that the three variables have a significant influence, both partially and simultaneously. Simultaneously, all three variables are able to explain 80% of the variation in purchase decisions. The study highlights the importance of data-driven promotion strategies in influencing consumer behavior, especially in non-urban areas Theoretical contribution/Originality : It lies in understanding how the twin-date event day, flash sale, and Shopee Live discount vouchers together influence purchasing decisions. This study explores the complex dynamics between these three factors and how the three promotions form consumer prevalence or perception so that it can influence consumer behavior to make purchase decisions. Practitionel/Policy implication : This research is expected to be able to provide practical implications, namely it can help companies formulate more appropriate advertising or promotion strategies to increase sales and customer satisfaction. Research limitation : The limitations of this study focus on a specific geographical area, so the results may not be able to be generalized to other regions or a wider area.